Local social innovation and welfare state restructuring: analysing their relationship - ImPRovE, Antwerp; Oosterlynck, Stijn; Kazepov, Yuri; Novy, Andreas; Cools, Pieter; Sarius, Tatiana; Wokuvitsch, Florian (Antwerp, 2015)
"This paper is concerned with local social innovation in the field of poverty reduction. We argue that local social innovation aimed at poverty reduction should be discussed in the context of the ongoing restructuring of the welfare state in Europe and debates about the future of social policy, paying particular attention to institutional features such as the territorial organization of the welfare system and changes in the welfare mix. Rather than seeing local social innovation as a new paradigm for social intervention that can potentially replace the welfare state, we see local social innovation as a wave of initiatives that is part and parcel of an ongoing spatio-institutional restructuring of welfare states, leading to a more complex rather than a completely different welfare mix.We start this paper with a general definition of social innovation as an innovation that is innovative both in its goals and means and then develop a more customised definition for the field of poverty reduction. We do so by discussing three core characteristics of social innovation in this area, namely its approach of poverty as a multidimensional and relational phenomenon, its critique of bureaucratic and centralized welfare institutions and its place-based character. This leads us to define local social innovations in the field of poverty reduction as locally embedded practices, actions and policies that enable socially excluded and impoverished individuals and social groups to satisfy basic needs for which they find no adequate solution in the private market or institutionalized macro-level welfare policies.In a final part of the paper, we build on this customized definition to analyze the relationship between social innovation and macro-level welfare state policies. We show how the spatio-institutional restructuring of welfare states in recent decades have created many points of contact between macro-level welfare policies and local social innovations and that recent and that social innovation has recently emerged on the European social agenda. Finally, by way of identifying issues of interest for empirical research on the relationship between social innovation and welfare state, we look at how local social innovations organize social interventions differently from conventional welfare state policies and social investment strategies."